The Effects of Workload and Work Environment on Local Police Performance: A Test of Work-related Stress' Mediating Effect - Arip Marianto (Britain International for Academic Research (BIAR) Publisher, 2021)
This research aims to analyze the influence of workload and work environment, mediated by work-related stress, on local police officers' performance. The population of this research was police officers of the Yapen Island Regency's Local Police, Papua region. The Slovin formula was used to determine the number of samples, and as many as 169 respondents were selected using a simple random sampling technique. A five-point Likert scale questionnaire was used as a research instrument. The SPSS Statistics was used to analyze the data. The analytical method used was descriptive analysis, validity and reliability tests, classical assumption tests, regression analysis, and mediation analysis using PROCESS macro by Hayes. The results showed that workload and work environment had a significant favorable influence on work-related stress. It also revealed that workload and work environment had a significant favorable influence on performance. Besides, work-related stress had a significant negative influence on performance. Work-related stress could mediate the relationship between workload and performance, while the relationship between work environment and performance could not be mediated by work-related stress. It implies that workload should be the improvement priority in designing the achievable performance target.